A global, spatially granular techno-economic analysis of offshore green ammonia production. (20th September 2022) - Salmon, Nicholas; Bañares-Alcántara, René
Abstract: Decarbonisation will see mass installation of wind turbines and solar panels to replace conventional energy systems. However, these renewables face two challenges: renewable energy production is intermittent, and land requirements are considerable. We propose a solution to both problems: production of green ammonia, a carbon-free fuel, in the ocean. Green ammonia can be produced from intermittent renewables, and can be dispatched as a hydrogen carrier, energy vector, shipping fuel, or decarbonised fertiliser. It is well suited to marine production — it benefits from the ocean's reliable wind resource, is easily transportable, can be stored cheaply under mild conditions, and only requires water, power and air for production. This article presents the first global heat map for ammonia production which considers ocean production, land availability restrictions, and transport to major demand centres. We show that, even considering the high costs of floating wind turbines, it is likely that cost savings will be realised by producing some of the global ammonia demand in the ocean (the precise fraction depends on the distribution of demand), predominantly because competition for land will limit onshore capacity in the best locations. Highlights: Offshore green ammonia production has no land constraints. Offshore green ammonia production has reliable wind resources. We present a global offshore LCOA heat map considering land availability. Offshore production may be financially competitive in the future.